2011
DOI: 10.1384/jsa.17.260
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of thin silicon films produced by metal-induced crystallization on insulating substrates by conductive AFM

Abstract: We applied conductive Atomic Force Microscopy (c-AFM) to characterize the electrical properties of low-temperature polycrystalline silicon. Current distribution and current-voltage characteristics are recorded using conductive-diamond covered AFM tip and low noise external amplifier. Spectroscopic ellipsometry and optical microscopy are used to determine the grain size, crystalline fraction and film thickness. The correlation between structural properties of the poly-Si fabricated with varied conditions and c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…the crystalline grains would conduct differently than the grain boundaries (or remaining amorphous phases), as it was observed in ref. [49].…”
Section: C-afm Investigation Of the Pinholes Formation Within The Siomentioning
confidence: 99%
“…the crystalline grains would conduct differently than the grain boundaries (or remaining amorphous phases), as it was observed in ref. [49].…”
Section: C-afm Investigation Of the Pinholes Formation Within The Siomentioning
confidence: 99%
“… 6 When the concentration of Al and Sn top metal is high at the grain boundaries, these insulating boundaries become electrically active and the resistivity of the film decreases. 38 It was observed that increasing the annealing time of the samples the electrical conductivity decreases from 40 Ω –1 m –1 corresponds to Al/Si/Sn annealed for 4 h to 0.4 Ω –1 m –1 corresponds to Al/Si/Sn annealed for 24 h. The reasons are that: (1) the increasing the bonding between Si atoms and the oxygen atoms in the membrane of the aluminum oxide as discussed above in FTIR analysis. The second reason is that (2) the annealing time assists the diffusion and solubility of tin.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the sample annealed for 8 h, the size of islands is larger (about 200–300 nm) as shown in Figure b and consequently smaller grain boundaries exist. This is caused by higher crystal growth in the sample annealed for 8 h than the other annealed for 4 h. , Selected area electron diffraction (SAED) shown in the insets of Figure a,b indicate the bright spots (crystallites) on the diffraction rings for the polycrystalline silicon and aluminum. For Al/Si/Sn samples, Figure a–d shows TEM micrographs of Al/Si/Sn nanocrystals annealed at 500 °C for 4, 8, 12, and 24 h. The accumulation of the crystallites is very small for the thin films annealed for 4 h. This accumulation increases in the films annealed for 8 h. In the sample annealed for 12 h, the accumulated crystallites forming island shapes increase as the annealing time duration increased and these islands shapes began to attach continuously to each other.…”
Section: Resultsmentioning
confidence: 99%
“…A low-temperature polysilicon (LTPS) is the polycrystalline silicon film formed by subsequent low-temperature crystallization of amorphous silicon (a-Si). Usually, there are two common methods for fabrication of LTPS film such as excimer laser annealing (ELA) [4] and metal induced crystallization (MIC) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The ELA method is currently used as a low-temperature manufacturing approach; however it needs expensive equipment to be implemented.…”
Section: Introductionmentioning
confidence: 99%